KEMAMPUAN KOMUNIKASI MATEMATIS SISWA DITINJAU DARI GAYA KOGNITIF DALAM MENYELESAIKAN SOAL MATEMATIKA MTS - Retno Restu Ningrum; Zubaidah Zubaidah; Dede Suratman (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractThis research aims to describe students' mathematical communication skills in solving refer to the Field Dependent cognitive style and Field Independent in solving cube and cuboid problems. The research method used is descriptive qualitative. The subjects of this study were 35 students of class IX H MTs Negeri 2 Pontianak. The data collection techniques used were Group Embedded Figures Test (GEFT) and written mathematical communication skills test questions. From the GEFT test results showed that 19 students ofField Dependent cognitive style and 16 students of Field Independent cognitive style. Based on the results of tests of mathematical communication skills, shows that students of cognitive style of Field Dependent were less able to convert mathematical ideas into images, do not have ideas or strategies so they cannot solve problems. Students of cognitive style of Field Independent were quite capable of changing mathematical ideas into image form, having ideas or strategies to solve problems, but the answer are less precise. Mathematical communication skills of students with Field Dependent cognitive style have moderate categories, and mathematical communication skills of students with Field Independent cognitive style have high categories. Keywords: Cognitive Style, Group Embedded Figures Test, Mathematical    Communication Skills